2019
DOI: 10.3390/cells8080930
|View full text |Cite
|
Sign up to set email alerts
|

EGFR–c-Src-Mediated HDAC3 Phosphorylation Exacerbates Invasion of Breast Cancer Cells

Abstract: Breast cancer is one of the leading causes of morbidity and mortality among women. Epidermal growth factor receptor (EGFR) and proto-oncogene tyrosine-protein kinase Src (c-Src) are critical components of the signaling pathways that are associated with breast cancer. However, the regulatory mechanism of histone deacetylase 3 (HDAC3) in these pathways remains unclear. Using the Net Phos 3.1 program for the analysis of kinase consensus motifs, we found two c-Src-mediated putative phosphorylation sites, tyrosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 50 publications
1
9
1
Order By: Relevance
“…In this study, we have demonstrated that the interaction between HIPK2 and HDAC3 was increased in LPS-treated macrophages, and HIPK2 phosphorylates HDAC3 at Ser374 to inactivate its deacetylase activity. So far, only four phosphorylation sites in HDAC3 have been identified to enhance its deacetylase activity, including Ser424 (phosphorylated by protein kinase CK2) (18), Tyr325, Tyr328, and Tyr331 (phosphorylated by proto-oncogene tyrosine-protein kinase Src) (46,47). In contrast, our study has identified phosphorylation of Ser374 as an inhibitory site to decreases the deacetylase activity of HDAC3.…”
Section: Discussioncontrasting
confidence: 53%
“…In this study, we have demonstrated that the interaction between HIPK2 and HDAC3 was increased in LPS-treated macrophages, and HIPK2 phosphorylates HDAC3 at Ser374 to inactivate its deacetylase activity. So far, only four phosphorylation sites in HDAC3 have been identified to enhance its deacetylase activity, including Ser424 (phosphorylated by protein kinase CK2) (18), Tyr325, Tyr328, and Tyr331 (phosphorylated by proto-oncogene tyrosine-protein kinase Src) (46,47). In contrast, our study has identified phosphorylation of Ser374 as an inhibitory site to decreases the deacetylase activity of HDAC3.…”
Section: Discussioncontrasting
confidence: 53%
“…SRC is a non-receptor tyrosine kinase family member with a crucial role in tumor progression. PP-2, an inhibitor of SRC, may signi cantly ameliorate the invasiveness of breast cancer cells and enhance the radiosensitivity of glioma cells [45,46]. Moreover, in our study, PP-2 showed therapeutic value in six HPVnegative HNSCC cell lines in vitro.…”
Section: Discussionsupporting
confidence: 56%
“…Thus, Src acts as an important oncogenic switch linked to the activity of growth factors receptors, including EGFR and HER2 [63]. Indeed, Src activation is a critical event in the signaling downstream EGFR during breast cancer progression, stimulating migration and invasion of surrounding tissues [64]. Several preclinical studies have successfully used an Src inhibitor in order to counteract the aggressive phenotype of HER2+ breast cancer lines.…”
Section: Breast Cancermentioning
confidence: 99%